Особливості біс-хелатних комплексів магнію(ІІ), як екологічно безпечних високоефективних змащувальних додатків нового покоління, в аспектах механохімії сталевої поверхні - Міщук, О.О.; Коваль, Л.І.; Дзюба, В.І.; Пехньо, В.І. (Доповіді НАН України, 2020)
У дослідженні виявлено особливий стан катіона магнію, з виникненням заборонених правилами відбору електронних переходів, у наношарі перехідного псевдокарбіду заліза, механохімічно утвореного у складі тертьового поверхневого шару сталі. Вивчено комплексну нанотонкоплівкову будову останнього. Зроблено висновок про можливість ефективної заміни мінеральних порошків серпентинітів — природних гідросилікатів магнію — синтетичними біс-хелатами магнію(ІІ) як змащувальними додатками нового покоління. The specific character of magnesium cation in the nanolayer of iron transitive pseudocarbide which is created tribochemically in the composition of tribofilm of the steel friction surface is found. This specific character of magnesium appears with the emergence of intraatomic electronic transitions which are forbidden by the selection rules. In particular, the magnesium cation can be used as an atomic probe to study the construction and origin of a friction surface layer (tribofilm). This work concerns the nanomechanicalchemical transformations of a steel friction surface layer of submicron thickness and the creation of a tribofilm. The complex nanothinlayer structure of the tribofilm is examined by the methods of SEM, EPMA, AES (submicroprobe), and argon ion nanoetching. It is found that the metal chelates which are synthesized by the authors, are the donors of a metal cation to a structure of quasiequilibrium undersurfacefriction nanolayers of iron pseudocarbide and nanooxide compounds. Finally, a conclusion of the opportunity to alternate effectively the mineral powders of serpentines — natural magnesium hydrosilicate — by the synthetic bischelate complexes of magnesium(II) as lubricating additives of a new generation is made. В исследовании обнаружено особенное состояние катиона магния, с появлением запрещенных правилами отбора электронных переходов, в нанослое переходного псевдокарбида железа, механохимически образованного в составе поверхностного слоя трения стали. Изучено комплексное нанотонкопленочное строение последнего. Сделан вывод о возможности эффективной замены минеральных порошков серпентинитов — природных гидросиликатов магния — синтетическими бис-хелатами магния(ІІ) как смазочными добавками нового поколения.